Amanita parvirufobrunnescens (Agaricales: Amanitaceae), a new species in A. sect. Amidella from India. (14th April 2021) - Kumar, Anil; Sharma, Yash Pal; Verma, Komal; Mehmood, Tahir
Abstract : Amanita parvirufobrunnescens, a new species of Amanita sect. Amidella is described here based on morphological and molecular evidence. This new species is recognized by its small sized basidiomata, snow‐white pileus covered by light grey to grey to brownish volval remnants on the pileus, context turning brownish to reddish‐brown on cutting or bruising, ellipsoid to elongated basidiospores measuring 10.0–17.0 × 6.0–10.0 μm and its occurrence in coniferous forests dominated by Abies pindrow and Picea smithiana . Morphological characters and molecular phylogenetic analyses based on the large subunit of nuclear ribosomal DNA (nrLSU) data support that the present species differs from other members of A . sect. Amidella . Description, discussion, drawings, photographs and a phylogenetic framework for the new species are given.